2011
DOI: 10.1371/journal.pone.0017916
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Quantitation in Complex Matrices: A Multi-Operator Comparison of DNA Extraction Methods with a Novel Assessment of PCR Inhibition

Abstract: Background Mycobacterium bovis is the aetiological agent of bovine tuberculosis (bTB), an important recrudescent zoonosis, significantly increasing in British herds in recent years. Wildlife reservoirs have been identified for this disease but the mode of transmission to cattle remains unclear. There is evidence that viable M. bovis cells can survive in soil and faeces for over a year.Methodology/Principal FindingsWe report a multi-operator blinded trial for a rigorous comparison of five DNA extraction methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 31 publications
4
58
1
Order By: Relevance
“…This process, however, adds time and expense to the method and does not necessarily ensure the elimination of all inhibitory factors. A recent study demonstrated that a new commercially available PCR reagent formulation, TaqMan Ò Environmental Master Mix, was successful in amplifying and detecting target sequences in purified DNA extracts of a number of fecal samples that were recalcitrant to analysis by Universal Master Mix (Pontiroli et al, 2011). In the present study, none of the undiluted Ohio River water sample extracts failed the Sketa22 SPC assay acceptance criteria in analyses using Environmental Master Mix as compared to an 18% failure rate with Universal Master Mix.…”
Section: Discussionmentioning
confidence: 50%
“…This process, however, adds time and expense to the method and does not necessarily ensure the elimination of all inhibitory factors. A recent study demonstrated that a new commercially available PCR reagent formulation, TaqMan Ò Environmental Master Mix, was successful in amplifying and detecting target sequences in purified DNA extracts of a number of fecal samples that were recalcitrant to analysis by Universal Master Mix (Pontiroli et al, 2011). In the present study, none of the undiluted Ohio River water sample extracts failed the Sketa22 SPC assay acceptance criteria in analyses using Environmental Master Mix as compared to an 18% failure rate with Universal Master Mix.…”
Section: Discussionmentioning
confidence: 50%
“…The extraction rates for the other methods were significantly better, but each method had distinctive features depending on the principle of purification and the parasite burden. The two kits using silica columns, i.e., QIAamp DNA Mini and NucleoSpin kits, were characterized by higher saturation limits than the methods based on magnetic silica, as already observed for Mycobacterium (32), while NucliSENS easyMAG gave higher extraction yields with fecal samples containing low parasite burdens. Curiously, NucliSENS easyMAG demonstrated a better extraction rate with fecal samples than with saline suspensions of oocysts.…”
Section: Discussionmentioning
confidence: 55%
“…A total of 25 soil samples recovered from six different geographical locations (Algeria, United Kingdom, Germany, Denmark, Norway, and Spain) and soil uses (agricultural and nonagricultural) were analyzed, including 10 samples collected in previous studies (17)(18)(19)(20)(21)(22)(23)) (Table 1). Fifteen samples were collected in this study from 0-to 15-cm depth using sterile plastic bags and stored at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%